Parametric performance assessment of RC columns retrofitted by CFRP - Abhishek Budhathoki,; Bhupendra Joshi,; Bigyan Acharya,; Basanta Baral,; Arjun Poudel,; Dipendra Gautam, (Advances in Engineering and Technology: An International Journal, 2023)
Retrofitting deficient columns requires meticulous efforts and most of the retrofitting techniques gravely increase the size of the member. Many studies have performed numerical and experimental studies regarding the performance of various retrofitting techniques. However, carbon fiber reinforced polymer (CFRP) as a retrofitting technique is seldom considered in parametric studies so as to quantify the axial load and maximum stress capacity of reinforced concrete (RC) columns. To this end, we perform parametric analysis considering variation in load eccentricities and no. of CFRP plies. Finite element modeling is conducted to assess the performance of non-retrofitted and CFRP retrofitted columns. We conclude that CFRP retrofitting significantly increases axial load as well as stress capacity of RC columns even for eccentric loading. .